Typical Forms of Plans for Certain Investigative (Search) Actions (Bulletin of Kharkiv National University of Internal Affairs, 2020)
Based on the analysis of the state of scientific research in regard to the provision of forensic recommendations on possible forms of planning the conduct of certain investigative (search) actions, the author has grounded the need to optimize its forms based on the technology of planning certain investigative (search) actions and the author has suggested own versions of a typical detailed written plan of investigative (search) actions and a concise written plan of investigative (search) actions. Taking into account the individual features of investigative (search) actions of certain types, the author has offered standard forms of interrogation plans, simultaneous interrogation of two or more already interrogated persons (face-to-face interrogation) and search in case of its conduct in the presence of the searched person.The most typical forms of plans for conducting certain investigative (search) actions are imaginary and written. The written plan can be concise or detailed. At the same time, a plan is always the result of planning as the process, nevertheless its form. Therefore, it must reflect the elements of this activity, set out in a certain sequence: 1) the situation of investigative (search) action; 2) versions explaining the situation; 3) tasks for each situation; 4) materials (evidence) available to the investigator; 5) organizational and tactical means of solving tasks.The variety of investigative (search) actions, their individuality requires a differentiated approach to the choice of the form of the plan in any particular case, because the overall scheme may undergo certain changes. In particular, in case of investigative (search) actions, where the preparation of a detailed written plan for their implementation at the preparatory stage is impossible due to the lack of sufficient information base or its inexpediency due to the lack of time, the following form of plan is possible:An individual approach to planning should be taken into account while drawing up plans of investigative (search) actions. For example, taking into account the specifics of the interrogation, its written plan may include the following elements: a) the circumstances to be clarified; b) the situation of interrogation; c) versions explaining the situation; d) tasks on the situation; e) questions to the interrogated person; e) the procedure for presenting evidence and other tactics; f) materials (evidence) available to the investigation.The written detailed plan of simultaneous interrogation of two or more already interrogated persons (face-to-face interrogation) may include the following elements: a) the situation of simultaneous interrogation of two or more already interrogated persons; b) versions of the reasons for the contradictions in the testimony; c) tasks to clarify them; d) questions to the interrogated person; e) the procedure for presenting evidence and other tactics; e) materials (evidence) available to the investigation.Carrying out a search in the presence of the searched person may include the following elements: a) search situation; b) versions explaining the situation; c) tasks on the situation; d) tactics; e) sequence of search actions; e) distribution of functions of search participants.